Greek tyranny - Lewis, Sian (Greece and Rome live, 2009)
The tyrants of Greece are some of the most colourful figures in antiquity, notorious for their luxury, excess and violence, and provoking heated debates among political thinkers. This book examines the phenomenon of autocratic rule outside the law in archaic and classical Greece, offering a new interpretation of the nature of tyranny